2022
DOI: 10.18006/2022.10(4).840.845
|View full text |Cite
|
Sign up to set email alerts
|

In-silico designing of a potent ligand molecule against PTEN (Phosphatase and tensin homolog) implicated in Breast Cancer

Abstract: Breast cancer has been attributed to be the second most common malignancy in females worldwide after skin cancer associated with a significantly high mortality rate. Tumor suppressor genes have an indispensable role in maintaining genomic integrity as well as cell cycle regulation. Phosphatase and tensin homolog deleted on chromosome ten (PTEN) is one of the most frequently mutated human tumor suppressor genes, implicated in cell growth, survival, and suppressing tumor formation. As the tumor progresses to mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Based on our experimental calculations on ligand binding free energy, favoured interactions with protein atoms, the results of the study are consistent with those found in the existing literature. 31…”
Section: Docking Via Auto Dockmentioning
confidence: 99%
“…Based on our experimental calculations on ligand binding free energy, favoured interactions with protein atoms, the results of the study are consistent with those found in the existing literature. 31…”
Section: Docking Via Auto Dockmentioning
confidence: 99%
“…The cleft is shaped like a deep V, thanks to the FRB or FKBP12-rapamycin-binding domain, which also limits access to the substrate-binding region (Ram et al 2020). When rapamycin-FKBP12 binds to the FRB (Raghav et al 2022), it effectively blocks all access to the substrate-binding site (Sharma et al 2010). Besides aiding in a restriction to the active site, FRB also facilitates S6K1 (a ribosomal protein kinase) access to the active site, yielding increased kinase activity (Raghav et al 2020).…”
Section: Introductionmentioning
confidence: 99%